The Impact of the Roman Empire on Landscapes Proceedings of the Fourteenth Workshop of the International Network Impact of Empire (Mainz, June 12-15, 2019) - Horster, Marietta; Hächler, Nikolas (Impact of Empire, 2022)
This volume presents the results of the fourteenth workshop of the international network 'Impact of Empire'. It focuses on the ways in which Rome's dominance influenced, changed, and created landscapes, and in which ways (Roman) landscapes were narrated and semantically represented.; Readership: This publication will be of particular interest for institutions promoting Greek and Roman studies and for scholars and students of classical and archaeological studies, who explore the Roman Empire.